Impact of the isoelectric point of model parvoviruses on viral retention in anion‐exchange chromatography. Issue 1 (12th September 2020) - Leisi, Remo; Wolfisberg, Raphael; Nowak, Thomas; Caliaro, Oliver; Hemmerle, Andreas; Roth, Nathan J.; Ros, Carlos
Abstract: Anion‐exchange chromatography (AEX) is used in the downstream purification of monoclonal antibodies to remove impurities and potential viral contamination based on electrostatic interactions. Although the isoelectric point (pI) of viruses is considered a key factor predicting the virus adsorption to the resin, the precise molecular mechanisms involved remain unclear. To address this question, we compared structurally homologous parvoviruses that only differ in their surface charge distribution. A single charged amino acid substitution on the capsid surface of minute virus of mice (MVM) provoked an increased apparent pI (pIapp ) 6.2 compared to wild‐type MVM (pIapp  = 4.5), as determined by chromatofocusing. Despite their radically different pIapp, both viruses displayed the same interaction profile in Mono Q AEX at different pH conditions. In contrast, the closely related canine parvovirus (pIapp  = 5.3) displayed a significantly different interaction at pH 5. The detailed structural analysis of the intricate three‐dimensional structure of the capsids suggests that the charge distribution is critical, and more relevant than the pI, in controlling the interaction of a virus with the chromatographic resin. This study contributes to a better understanding of the molecular mechanisms governing virus clearance by AEX, which is crucial to enable robust process design and maximize safety. Abstract : In this study, the molecular basis of the electrostatic interaction of nonenveloped viruses with anion‐exchange chromatography (AEX) resins was investigated. To this end, the precise chromatographic behavior of structurally homologous capsids differing in surface charge distribution and isoelectric point (pI) was compared. The results revealed that the distribution, as well as the surface accessibility of charges in the three‐dimensional structure of the capsid, are critical, and more relevant than the pI, in controlling the interaction of the viral particle with the chromatographic resin.